Aquatic ecosystem changes in a global biodiversity hotspot: Evidence from the Albertine Rift, central Africa - McGlynn, Gayle; Lejju, Julius; Dalton, Catherine; Mooney, Scott D.; Rose, Neil L.; Tompkins, Adrian M.; Bannister, Wayne; Tan, Zu D.; Zheng, Xianglin; Rühland, Katherine M.; Taylor, David (Journal of Biogeography, 2019)
Determine the extent to which remote, high‐altitude (Afroalpine) aquatic ecosystems in tropical Africa have been impacted by global and regional‐scale environmental change processes. Location: Two volcanic crater lakes (Bisoke and Muhavura) in the Afroalpine zone, Albertine (Western) Rift, central Africa. Methods: Sediment cores were collected from Bisoke and Muhavura lakes and dated using radiometric techniques. A range of sediment‐based proxies was extracted from the cores and quantified. Sedimentary data were subjected to statistical analyses that contributed to the identification of influential environmental variables and their effects on diatom assemblages, the determination of variations in spatial beta diversity and estimates of the rate of compositional turnover over the last c. 1,200 years. Results: Sediments from the two sites provide evidence of the sensitivity of remote, Afroalpine aquatic ecosystems to perturbation. Climate variability has been a major driver of ecological change, particularly at Bisoke Lake, throughout the c. 1,200‐ year‐long record, while Muhavura Lake has been directly impacted by and recovered from at least one volcanic eruption during this time. The effects of climatic warming from the mid‐ to late 19th century and especially from the late 20th century, possibly accentuated by atmospheric deposition‐driven nutrient enrichment, appear increasingly in lockstep. Effects include changes in diatom community composition, increased productivity and compositional turnover, and biotic homogenization (reduced spatial beta diversity) between the two sites. Main conclusions: The two Afroalpine sites record changes in atmospheric conditions and their effects on diatom assemblage composition, particularly over the last c. 150 years. Drivers of these changes have the potential to disrupt ecosystems at lower altitudes in the Albertine Rift, including biodiverse areas of forest, and across tropical Africa more widely.
Keywords: Afroalpine; Atmospheric deposition; Biotic homogenization; Climate change; Eutrophication; Pollution